PENGARUH PROGRAM KAMPUS MENGAJAR DAN INTERNAL LOCUS OF CONTROL TERHADAP MINAT MENJADI GURU BAGI MAHASISWA S1 JURUSAN PENDIDIKAN EKONOMI UNIVERSITAS NEGERI SURABAYA - Ihkam Najahi Tsani; Tri Sudarwanto (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
This study aims to determine the effect of the Teaching Campus Program and Internal Locus Of Control partially on the Interest to Be a Teacher and to determine the effect of the Teaching Campus Program and Internal Locus Of Control simultaneously or together on the interest in becoming a teacher. This research uses descriptive quantitative. The population of this study were students of the Surabaya State University Economics Education Department using the Purposive Sampling technique using the Slovin formula with the results of 126 students from Surabaya State University consisting of the Economics Education Study Program, Office Administration Education, Accounting Education and Commerce Education. Data collected via google form was measured with a Likert scale using the IBM 22 version of SPSS software with multiple linear regression analysis methods. The results of this study indicate that partially there is a positive influence between the Teaching Campus Program on the Interest to Become a Teacher and there is a positive influence between the Internal Locus of Control on the Interest to Become a Teacher. As well as the results of the study explain that simultaneously there is a positive influence between the Teaching Campus Program and the Internal Locus Of Control on the Interest to Be a Teacher. Keywords : Teaching Campus Program, Internal Locus Of Control, Interest in Becoming a Teacher